2014
DOI: 10.1080/10376178.2014.11081906
|View full text |Cite
|
Sign up to set email alerts
|

A patient safety focused registered nurse transition to practice program

Abstract: New graduate registered nurses (NGRN's) have an expectation of clinical support as they make the transition from novice to advanced beginner. In this 2008-2009 study of three rural transition to practice programs we found that clinical support did not eventuate. Consequently, NGRN's reported feeling underprepared for practice, overwhelmed by responsibility and often abandoned. Against this background, many were concerned that their inexperience had implications for safe patient care. Graduate nurse transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…After meeting with limited success they were more willing to open up to others and seek additional support. It is possible to achieve excellent results with knowledge of the support networks available and thereby avoid feeling overwhelmed (Mellor & Greenhill, 2014). Natasha did this: For example, a situation can be de-escalated when the NGRN actively listens to the doctor, provides an understanding response and maintains a calm demeanour.…”
Section: Ways I Navigatementioning
confidence: 99%
“…After meeting with limited success they were more willing to open up to others and seek additional support. It is possible to achieve excellent results with knowledge of the support networks available and thereby avoid feeling overwhelmed (Mellor & Greenhill, 2014). Natasha did this: For example, a situation can be de-escalated when the NGRN actively listens to the doctor, provides an understanding response and maintains a calm demeanour.…”
Section: Ways I Navigatementioning
confidence: 99%
“…However ineffective transition may cause new nurses feelings of helplessness. On the grounded theory study, Mellor & Greenhill (2014) claimed that new nurses in transition to practice reported to have feelings of underprepared for practice, overwhelmed by responsibility, and often abandoned when clinical support did not occur. Preceptors serving as role models to students must facilitate their teachinglearning process and socialization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As they entered their roles, participants went through many initial challenges, such as learning the expectations associated with their roles, balancing coursework and clinical responsibilities, developing professional relationships, and making independent decisions for the first time. Research examining the challenges associated with initial entry into the role of a certified AT is lacking; however, many investigators have addressed this transition in health care fields such as nursing [40][41][42][43] and physical therapy. [44][45][46][47] Similar to what the participants reported, many new nurses and physical therapists (PTs) felt overwhelmed as they encountered new challenges in their roles and had trouble balancing all their responsibilities.…”
Section: Initial Entry Into Rolementioning
confidence: 99%